Effectiveness of Narcotics Investigations in Central Sulawesi: A Procedural and Evidentiary Assessment under KUHAP and the Narcotics Law - Firmansyah Fality; Mulyati Pawennei; Hardianto Djanggih (Fakultas Hukum, Universitas Muslim Indonesia, 2025)
This study examines the effectiveness of narcotics crime investigations within the jurisdiction of the Central Sulawesi Regional Police through a procedural and evidentiary lens. Narcotics crimes pose a serious and evolving threat, requiring law enforcement responses that are legally sound, professional, and outcome-oriented. Using an empirical juridical approach with a descriptive-analytical design, the research analyzes the implementation of investigative stages, from inquiry, case exposition, to formal investigation, under Indonesia’s Criminal Procedure Code (KUHAP), the Narcotics Law, the Police Law, and Police Regulation No. 6 of 2019. Primary data were collected through interviews with narcotics investigators and questionnaires capturing perceptions of investigative effectiveness, while secondary data were drawn from legislation, scholarly literature, and prior studies. The findings indicate that, although procedural compliance and case-completion rates are relatively high, particularly in high-burden areas such as Palu City, investigative effectiveness is constrained by limited personnel capacity, uneven technical expertise, low public literacy on narcotics, and risks of intimidation against investigators. These constraints contribute to a gap between administrative outputs and perceived social impact. The study concludes that investigative effectiveness should be measured not merely by arrest numbers or case completion, but by procedural integrity, evidentiary resilience, human rights protection, and tangible disruption of narcotics networks.